Quality of preventive consulting on cardiovascular risk factors at primary healthcare level - A. M. Kalinina; A. V. Kontsevaya; M. G. Omelyanenko (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To assess the quality of preventive consulting (PC) on non-communicable disease (NCD) risk factors (RF) at primary healthcare level, on the basis of medico-sociologic survey among working6age visitors of territorial ambulatory and out-patient departments.Material and methods. The study was performed as a part of multi-center marketing survey of demand for doctoral PC on main NCD and their RF at two centers – territorial polyclinics in Moscow and Ivanovo. A special questionnaire was used for the survey of representative working-age patients of these polyclinics (men aged 20-59 years, women aged 20-54 years). In total, 641 subjects were included in the study.Results. Four quantitative PC quality parameters were proposed and assessed in the real-practice settings – indicators of preventive service quality (availability, accessibility, satisfaction) – RF awareness, demand for, reach of, and satisfaction by PC. The patients were inadequately aware on their own RF, with high demand and readiness for doctoral PC recommendations, and low PC reach: in every fifth case only, the already formed motivation anddemand for lifestyle modification could be satisfied.Conclusion. The study demonstrated inadequate PC quality and use of primary healthcare resources (direct patient-doctor contacts) for complex PC on main NCD RF.